Uwarunkowania rozwoju sektora małych i średnich przedsiębiorstw w Polsce - Chądrzyński, Mariusz (Conditioning the Development of the Sector of Small- and Medium-Sized Enterprises in Poland, 2009)
The paper is an attempt to introduce and classify factors affecting the functioning and development of small and medium enterprises in Poland. The author describes chosen constructive and destructive determinants that have an impact on the development of small and medium enterprises in Poland. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 1, s. 541-551